Two new species of Otiorhynchus Germar, 1822 of the subgenus Anchorrhynchus Reitter, 1914 from the Balkan Peninsula, with a key to species (Coleoptera: Curculionidae: Entiminae) - Szénási, Valentin (Zootaxa, 2022)
Otiorhynchus roznerantii Szénási sp. nov. from Greece and Republic of North Macedonia, and O. pseudoschlaeflini Szénási sp. nov. from Greece are described in the subgenus Anchorrhynchus Reitter, 1914. A provisional identification key to species of Anchorrhynchus is included, from which are excluded Otiorhynchus lumensis gjallicanus Lona, 1939, O. lumensis lumensis Apfelbeck, 1908, O. munelensis Apfelbeck, 1907 and O. pseudalbanicus Braun, 1990 which are here moved to Otiorhynchus incertae sedis, plus O. cypricola Reiche & Saulcy, 1858 specimens of which were unavailable.